Nanoscale architecture of cadherin-based cell adhesions - Bertocchi, Cristina; Wang, Yilin; Ravasio, Andrea; Hara, Yusuke; Wu, Yao; Sailov, Talgat; Baird, Michelle A.; Davidson, Michael W.; Zaidel-Bar, Ronen; Toyama, Yusuke; Ladoux, Benoît; Mege, Rene Marc; et al. (Nature Cell Biology, 2017)
Multicellularity in animals requires dynamic maintenance of cell-cell contacts. Intercellularly ligated cadherins recruit numerous proteins to form supramolecular complexes that connect with the actin cytoskeleton and support force transmission. However, the molecular organization within such structures remains unknown. Here we mapped protein organization in cadherin-based adhesions by super-resolution microscopy, revealing a multi-compartment nanoscale architecture, with the plasma-membrane-proximal cadherin-catenin compartment segregated from the actin cytoskeletal compartment, bridged by an interface zone containing vinculin. Vinculin position is determined by α-catenin, and following activation, vinculin can extend â 1/430 nm to bridge the cadherin-catenin and actin compartments, while modulating the nanoscale positions of the actin regulators zyxin and VASP. Vinculin conformational activation requires tension and tyrosine phosphorylation, regulated by Abl kinase and PTP1B phosphatase. Such modular architecture provides a structural framework for mechanical and biochemical signal integration by vinculin, which may differentially engage cadherin-catenin complexes with the actomyosin machinery to regulate cell adhesions.
CRIS-Team Scopus Importer:2024-02-19